Static and Dynamic Scaling Close to Gelation in Chain‐Polymerization: Effect of Reactor Type. Issue 3 (18th April 2017) - Das, Chinmay; Read, Daniel J.; Soulages, Johannes M.; Shirodkar, Pradeep P.
Abstract : Copolymerization of two and four functional groups in semibatch reactor leads to diverging weight averaged molar mass and zero shear viscosity with an exponent −4.5 as gelation is approached with increasing amount of four functional groups. In contrast, in continuous stirred tank reactor, the number, weight, and z ‐averaged molar masses remain finite and viscosity diverges with an exponent −1.2. Abstract : Because of the familiarity of gelation theories in polycondensation reaction of multifunctional groups, often the gel‐point is defined as the point of diverging weight averaged molar mass. The authors present an industrially relevant counter‐example to this common perception. Chain‐growth polymerization in realistic reactors introduces history dependent crosslinking probability. For copolymerization of a two functional monomer (ethylene) with a four functional comonomer (nonconjugated diene), the authors show from a Monte Carlo scheme that standard gelation scaling exponents remain valid for a semibatch reactor. However, for syntheses in a continuous stirred tank reactor (CSTR), all commonly measured molar mass moments (number, weight and " z "‐averaged moment) remain finite at the gel‐point; the first moment to diverge is the fourth moment. Hence, identification of the gel point from experimental observations is difficult, and cannot be achieved through monitoring of the weight averaged molar mass. The authors use a numerical scheme based on the tube model of polymer melts to predict the rheology of the generated molecules. Stress relaxation follows a power‐law decay, but due to dynamic dilution effects the CSTR resins exhibit much slower increase in the zero shear viscosity as the gel point is approached as compared to the semibatch reactor resins.